Protective role of ginseng extract against oxidative stress, reproductive and some biochemical parameters alterations induced by doxorubicin in male rats - Kassem, Mohammed; Ali, Abdel-Fattah; Abo-kora, Seham Y.; Shawky, Nesreen (International Journal of Pharmacology and Toxicology, 2020)
This study investigates the modulating effect of ginseng against testicular toxicity, oxidative stress and changes in some biochemical parameters induced by doxorubicin. Twenty male rats were divided into four groups. The 1st group received distilled water orally (control group), The 2nd group received doxorubicin (5 mg/kg b.wt. intrapertenoineal) once a week for eight weeks, The 3rd group received ginseng extract (200 mg/kg b.wt.) daily for eight weeks and the 4th group received doxorubicin with ginseng extract by the same doses as in the 2nd and the 3rd groups respectively. At the end of the 8th week, blood and semen samples were taken for biochemical and semen analysis, respectively. The doxorubicin treated group had significantly higher serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), Creatine kinase (CK) and lactate dehydrogenase (LDH) along with lower levels of total protein, albumin and globulin. In addition, a significant decrease in antioxidant enzymes (SOD, CAT, GSHPx), and glutathione (GSH) associated with higher level of malondialdehyde (MDA) were observed. At the same time, the group that took doxorubicin with ginseng did not differ from control group in terms of these parameters. Male fertility study showed changes in testosterone and semen analysis in both groups treated with doxorubicin, while the group that took doxorubicin with ginseng showed an improvement towards control levels of these parameters. Thus ginseng supplement can reduce the negative effects of doxorubicin- induce. Â Â